2020
DOI: 10.3389/fpsyg.2020.579155
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Measurement of Work-Related Age Attitudes and Age Stereotypes

Abstract: Age attitudes and age stereotypes in the workplace can lead to discrimination and impaired productivity. Previous studies have predominantly assessed age stereotypes with explicit measures. However, sole explicit measurement is insufficient because of social desirability and potential inaccessibility of stereotypical age evaluations to introspection. We aimed to advance the implicit and explicit assessment of work-related evaluations of age groups and age stereotypes and report data collected in three samples:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In line with the literature (e.g. Kleissner and Jahn, 2020), the participants who first performed the stereotype-congruent block (modern work/younger workers) showed higher implicit modern-work-is-young stereotypes ( M D score = 0.84; large effect) than participants who performed the non-congruent block first ( M D score = 0.71; moderate effect), t (184) = −2.335, 95% CI [−0.23; −0.02], p = 0.021. According to Greenwald et al (2003), D scores can be interpreted by applying the criteria for effect sizes of Cohen’s (1977) d measure.…”
Section: Resultssupporting
confidence: 89%
“…In line with the literature (e.g. Kleissner and Jahn, 2020), the participants who first performed the stereotype-congruent block (modern work/younger workers) showed higher implicit modern-work-is-young stereotypes ( M D score = 0.84; large effect) than participants who performed the non-congruent block first ( M D score = 0.71; moderate effect), t (184) = −2.335, 95% CI [−0.23; −0.02], p = 0.021. According to Greenwald et al (2003), D scores can be interpreted by applying the criteria for effect sizes of Cohen’s (1977) d measure.…”
Section: Resultssupporting
confidence: 89%
“…Recent experimental studies confirm the existence and stability of age stereotypes. By measuring attitudes not explicitly, for example in self-report, but implicitly via the Implicit Association Test, it could be shown that younger workers are preferred to older workers by students, older adults and workers (Kleissner & Jahn, 2020b). Another point worth considering is discrimination through colleagues as a behavioural consequence of negative age stereotyping (Nelson, 2005).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Stereotypes exist about members of different socio‐demographic groups (e.g., based on one of the Big Three demographics: age, ethnicity, and gender). For example, older people are stereotypically viewed as unadaptable, inflexible, and stubborn, whereas younger aged people are stereotypically perceived as inexperienced, irresponsible, and lazy (Finkelstein et al, 2013; Kleissner & Jahn, 2020; Posthuma & Campion, 2009). Interestingly, group members may also contemplate which stereotypes others hold about them.…”
Section: Job Ads and Metastereotypesmentioning
confidence: 99%